2019
DOI: 10.3389/fnagi.2019.00323
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus Radiomic Biomarkers for the Diagnosis of Amnestic Mild Cognitive Impairment: A Machine Learning Method

Abstract: Background: Recent evidence suggests the presence of hippocampal neuroanatomical abnormalities in subjects of amnestic mild cognitive impairment (aMCI). Our study aimed to identify the radiomic biomarkers of the hippocampus for building the classification models in aMCI diagnosis.Methods: For this target, we recruited 42 subjects with aMCI and 44 normal controls (NC). The right and left hippocampi were segmented for each subject using an efficient learning-based method. Then, the radiomic analysis was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…The A.K software has been registered and approved. It realizes several key steps of radiomics and has already been applied to some radiomics studies, including ourselves (18,19). The image resolution was adjusted to 1 mm × 1 mm × 1 mm for resampling.…”
Section: Radiomics Analysismentioning
confidence: 99%
“…The A.K software has been registered and approved. It realizes several key steps of radiomics and has already been applied to some radiomics studies, including ourselves (18,19). The image resolution was adjusted to 1 mm × 1 mm × 1 mm for resampling.…”
Section: Radiomics Analysismentioning
confidence: 99%
“…The characteristics of the 26 included radiomics studies ( 12 13 14 15 16 17 19 20 21 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 ) are summarized in Table 1 , Figure 2 , and Supplementary Table 2 . The median number of subjects in the included articles was 204 (range 86–460).…”
Section: Resultsmentioning
confidence: 99%
“…The SVM had the best sensitivity (0.8458), whereas naïve Bayes had the best specificity (0.8158) and best accuracy (0.8329). Several pilot studies have used machine learning methods to predict MCI (Chiu et al, 2019; Feng et al, 2019; Khazaee et al, 2016). Feng et al used logistic regression models and hippocampus radiomics biomarkers, and reported that the AUC, specificity and sensitivity of the classification evaluation index of the right hippocampus logistic regression model were 0.76, 0.71 and 0.69, respectively (Feng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several pilot studies have used machine learning methods to predict MCI (Chiu et al, 2019; Feng et al, 2019; Khazaee et al, 2016). Feng et al used logistic regression models and hippocampus radiomics biomarkers, and reported that the AUC, specificity and sensitivity of the classification evaluation index of the right hippocampus logistic regression model were 0.76, 0.71 and 0.69, respectively (Feng et al, 2019). Khazaee et al applied machine learning methods on resting-state functional magnetic resonance imaging (fMRI) networks and observed that the classification accuracy for distinguishing MCI from healthy controls and AD was 72.0% (Khazaee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%